PROBLEMATIKA PENDIDIKAN MODERASI DALAM PEMIKIRAN WAHBAH AL-ZUHAILI - Abdul Majid, Zamakhsyari; Mulyati, Mumun (Almarhalah: Jurnal Pendidikan Islam, 2022)
This paper aims to examine and analyze the problems education of Islamic moderation from the viewpoint of Wahbah al-Zuhaili's Tafsir al-Munir and al-Fiqh al-Islamiy wa Adillatuhu science. The focus of the study in this paper is to analyze the moderate thoughts of Wahbah al-Zuhaili in understanding Islam through Tafsir al-Munir. Wahbah al-Zuhaili as a Muslim intellectual who mastered various scientific disciplines and had a moderate perspective. Wahbah al-Zuhaili's thoughts on moderation in Islamic law through his work al-Fiqh al-Islamiy wa Adilatuhu. In the book of al-Fiqh al-Islamiy wa Adillatuhu, indicators of moderation in Islamic law are a) Flexibility in Islamic Law, b) Renewal in Islamic Law, c) Views in Schools.